2003
DOI: 10.1093/ajcn/77.2.504
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, vitamin D, milk consumption, and hip fractures: a prospective study among postmenopausal women

Abstract: An adequate vitamin D intake is associated with a lower risk of osteoporotic hip fractures in postmenopausal women. Neither milk nor a high-calcium diet appears to reduce risk. Because women commonly consume less than the recommended intake of vitamin D, supplement use or dark fish consumption may be prudent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
180
0
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 287 publications
(198 citation statements)
references
References 53 publications
(67 reference statements)
9
180
0
7
Order By: Relevance
“…This finding is consistent with those of other investigations (Suzuki et al, 1997;Feskanich et al, 2003) even though, null associations have also been reported (Appleby et al, 2007). Fish (especially dark meat fish) constitute good sources of calcium (especially when edible bones are consumed) and vitamin D. Moreover, they are rich in o-3 fatty acids.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with those of other investigations (Suzuki et al, 1997;Feskanich et al, 2003) even though, null associations have also been reported (Appleby et al, 2007). Fish (especially dark meat fish) constitute good sources of calcium (especially when edible bones are consumed) and vitamin D. Moreover, they are rich in o-3 fatty acids.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, the association between calcium intake from usual diet, mainly in the form of dairy products, and fracture risk among middle aged and elderly populations remains inconclusive (Weinsier and Krumdieck, 2000;Prentice, 2004). Observational epidemiological studies have shown that in countries with average mean calcium intakes, no association between calcium intake and hip fracture risk is apparent in older men and women (Kato et al, 2000;Weinsier and Krumdieck, 2000;Feskanich et al, 2003;WHO, 2003;Bischoff-Ferrari et al, 2007), whereas in populations with low mean calcium intakes, an increased risk of hip fractures with declining calcium intake (below around 400-500 mg of calcium/day) has been reported. On the other hand, the beneficial effect of combined calcium and vitamin D supplementation for fracture prevention in the frail elderly population is considered as documented and constitutes a recommended intervention against bone loss (Kannus et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, in the Nurses' Health Study, the exclusion of women with a history of diagnosed osteoporosis did not appreciably affect the association between milk intake and fracture risk. (29) Further, in data provided by Feskanich and colleagues for the Nurses' Health Study, milk accounted for 54% of dairy calcium intake, although this may be lower in some European countries where cheese is a stronger contributor to dairy calcium intake. (30)(31)(32) However, a lower dairy intake from milk in Europe would not have affected the results of this meta-analysis provided that milk intake is a relevant predictor of hip fracture risk overall.…”
Section: Discussionmentioning
confidence: 99%
“…Mean follow-up varied between 3 and 26 years. Three studies were from the United States, (10,22,23) two from Scandinavia, (24,25) one from Japan, (26) and one multicenter pooled project from 11 cohorts around the world (Europe, Australia, and Canada). (27) Primary analyses Figure 2A shows the Forest plots for the RR of hip fracture for a 1 glass increment of total daily milk intake among women.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation